Double infection by Multi-Drug Resistant Escherichia coli bacteria: A case report - Paramita, Ayu Lidya; Ievani, Yelvi (Jurnal Medis Islam Internasional, 2024)
Introduction: Antimicrobial resistance (AMR) is a global issue causing multidrug-resistant bacterial infections, leading to higher morbidity and mortality rates. Escherichia coli, a Gram-negative Enterobacterales bacteria, is the predominant cause of common diseases. In 2018, Escherichia coli ESBL (beta-lactamase enzyme Extended-spectrum) bacterium had the highest antibiotic resistance in Surabaya, Indonesia. In 2022, 3rd generation cephalosporin-resistant E. coli and carbapenem-resistant E. coli were the top priority pathogens in Indonesia. Case: A one-year-old girl was taken to the emergency room after vomiting seven times and vomiting. She had a fever for one week, and her nose was runny. The patient had kidney channels narrowed and had surgery to implant a DJ stent in her right kidney five months prior. Physical examination revealed anemia, jaundice, cyanosis, and dyspnea. Blood and urine cultures were conducted, and Escherichia coli bacteria were found in urine and blood samples. Escherichia coli ESBL was found to be sensitive to several drugs, while its blood showed it was carbapenem-resistant, only sensitive to Ceftazidim, Amikacin, Gentamicin, Tigecycline, and Cefoperazone Sulbactam. Discussion: Pediatric patients often experience urinary infections from Escherichia coli (ESBL) and bloodstream infections from Escherichia coli (CRE). These bacteria colonize various sites in the human body, including the urinary tract, causing diarrhea and causing cystitis. ESBL, or Extended Spectrum b-lactamase, breaks down antibiotics, making them ineffective for treating infections. ESBL production is associated with a bacterium found in the bowel, and resistance genes are often transmitted through plasmids carrying other resistance genes. The emergence of carbapenem-resistant Escherichia coli isolates (CREC) has led to using polymyxin, tigecycline, fosfomycin, and aminoglycosides as effective antibiotics against CREC. CREC can lead to severe infections, including intra-abdominal infections, pneumonia, urinary tract infections, and device-associated infections. Conclusions: Escherichia coli, an MDRO bacteria, requires antibiotic sensitivity test results for effective treatment, with sensitive drugs often chosen in difficult cases, and requiring source control.